Cordyceps militaris (L.) Link: Chemical Bioactive Compounds and Pharmacological Activities - Do Hai Lan; Nguyen Thi Kim Thu; Pham Thi Lan; Pham Van Nha; Bui Thanh Tung (Journal of Pharmacy and Nutrition Sciences, 2016)
Cordyceps militaris (L.) Link is an important medicinal mushroom used in traditional medicine for treatment of many diseases and improving human health. C. militaris are now widely used in many modern pharmaceutical dosages. It contains many bioactive compounds such as cordycepin, adenosine, sterols, polysaccharides, etc. These compounds provided many beneficial biological activities such as anticancer, antiproliferative, pro-sexual, antioxidant, antibacterial, antifungal, antiviral, immunomodulatory, antiinflammatory and others for C. militaris. The present review highlights the chemical bioactive compounds and pharmacological activities of this medicinal mushroom C. militaris.